EVALUATION PROCESSES IN HIGHER EDUCATION: THE TEACHING PLANS IN ANALYSIS - Taíze dos Santos Batistti; Valdete Moser Preto; Marcia Regina Selpa Heinzle (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
The general objective of this study was to analyze the evaluative processes present in the teaching plan of a Bachelor's Degree in Visual Arts. Therefore, data collection was done by reading the teaching plans of a course of a Higher Education Institution, located in the city of Blumenau, State of Santa Catarina, Brazil. Documentary analysis was based on André and Ludke. In relation to the data analysis, we dialogued with the theoretical contribution of the following authors: Barbosa, Hernandez, Luckesi, Hoffmann and Zabala. Among the main results, we identified a diverse number of instruments, which are in accordance with the procedural contents. Among the criteria, the evaluation of procedural and attitudinal contents predominates. In the specific objectives, the emphasis is on conceptual content. The evaluation processes contained in the teaching plans of the Visual Arts course allowed us to reflect on the autonomy of teachers and the evaluation in Higher Education that reveal approximations with the perspective of mediator evaluation and its formative function. We also understand that the various evaluation instruments emphasize, in their majority, a relation with the artistic practices developed in the process of teaching and learning.